CRIMINAL LAW ENFORCEMENT ANALYSIS AGAINST INDEPENDENT PRACTICE MIDWIVES IN COMMITTING UNLAWFUL ACTS - Ayu Endang Astuti; Aan Asphianto; Mohamad Noor Fajar Al Arif (Universitas Muhammadiyah Tangerang, 2022)
The phenomenon of maternal and infant mortality in Banten Province is still high. Based on data released by the United States Agency for International Development (USAID) Jalin, in Banten Province every week there are an average of 5 mothers and 27 newborns who die the highest deaths are in Pandeglang Regency with 59 cases. and when the public's need for health services increases, especially midwife services, it is not balanced by the expertise and skills of midwives to form a good service work mechanism. So often we also find midwife services not in accordance with their authority. The problems that the author will discuss are related tothe criminal law enforcement of the actions of midwives who are against the law and the authority of independent practice services in Pandeglang Regency and theimplementation of legal policies regarding criminal acts in cases of malpractice in Pandeglang Regency. The method used in this study is a normative juridical descriptive method using a problem approach with the Law by prioritizing primary data and secondary data. The results of this study that midwives who carry out obstetric services are not in accordance with applicable regulations, will be sanctioned in accordance with the Minister of Health of the Republic of Indonesia Number. 1464/Menkes/PER/X/2010 on the licensing and administration of midwife practices. Sanctions given to midwives can be in the form of revocation of the midwife's practice license, revocation of Surat Izin Praktek Bidan temporary, or it can also be a fine. In addition, midwives can also be sentenced to prison if they violate the laws and regulations. If a midwife violates the code of ethics, the settlement of this matter is carried out by the midwife professional forum, namely the Midwife Professional Council or the Indonesian Midwife association.Keywords: Law Enforcement, Midwives, and Unlawful Acts